2018
DOI: 10.1039/c8dt02239a
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide extraction selectivity of a tripodal carbamoylmethylphosphine oxide ligand system

Abstract: Four tripodal carbamoylmethylphosphine oxide (CMPO)-based ligands are reported here and assessed with regard to lanthanide (Ln) coordination chemistry and selective extraction of lanthanide ions from aqueous solution. Inspired by previous liquid-liquid extraction studies that suggested a preference for terbium(iii), the current work further probes the extraction behavior of a tris-(2-aminoethyl)amine (TREN) capped, ethoxy substituted CMPO ligand with respect to the entire series of lanthanides. Upon confirmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…During reactions under higher pH conditions (pH > 7), the CH 2 Cl 2 /water emulsion was found to quickly acidify, presumably due to liberation of acid caused by complex formation (eq , L = ligand). By tightly maintaining the appropriate pH of the emulsion (with NaOH), the time for completion of liquid–liquid extraction decreased to ∼1 h, which is significantly faster than many other reported ligands used in these processes …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During reactions under higher pH conditions (pH > 7), the CH 2 Cl 2 /water emulsion was found to quickly acidify, presumably due to liberation of acid caused by complex formation (eq , L = ligand). By tightly maintaining the appropriate pH of the emulsion (with NaOH), the time for completion of liquid–liquid extraction decreased to ∼1 h, which is significantly faster than many other reported ligands used in these processes …”
Section: Resultsmentioning
confidence: 99%
“…In this approach, organic ligands are dissolved in a nonpolar, water-immiscible solvent and are used to separate desired metal ions from aqueous solution. 54,65,66 As expected, when the pH of the aqueous layer was acidic (e.g., pH = 3, 1:1 CH 2 Cl 2 /H 2 O), virtually no extraction from the aqueous to organic layer was observed (<10%) during 24 h. However, as the pH of the solution was raised to pH > 5, as could be found in many secondary resource leachate streams, the ability of 1 to extract Ce increased significantly. At neutral or slightly basic pH values (i.e., pH = 8), 1 extracted 67% of Ce (CH 2 Cl 2 solution) at equilibrium (Figure 3A).…”
Section: Design Elements For Structured Multidentate Ligand Systems T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The final set of experiments our research group carried out to probe the solution behavior of these Ln-ligand complexes involved the characterization of their luminescence properties. We have previously studied a variety of multipodal ligands bearing this beta-phosphonate/phosphine oxide-amide chelating group, and we have shown that these types of compounds have the ability to sensitize the luminescence of Eu 3+ and Tb 3+ [ 32 , 33 , 34 ]. Ligands 1 and 2 described in this paper are also able to sensitize this luminescence, albeit to a modest extent.…”
Section: Resultsmentioning
confidence: 99%
“…29 Recent work in our laboratory has been geared toward developing preorganized, tripodal CMPO-based ligands using a modular synthetic approach that facilitates structural variation to tune the metal extraction selectivity. Since our initial report of enhanced Tb(III) extraction by the tris(2-aminoethyl)amine (TREN)capped TREN-CMPO-OEt ligand (1, Figure 1), 32 additional ligand caps and CMPO substituents have been explored (e.g., 2 and 3, Figure 1), 33,34 revealing relationships between structural variation and metal extraction. This study focuses on a new extraction agent possessing the tris(3-aminopropyl)amine (TRPN) ligand scaffold, TRPN-CMPO-Ph (4, Figure 1), and describes its f-element extraction behavior.…”
mentioning
confidence: 99%